(untitled) (Biological Sciences - PJSIR, 2023)
Malnutrition is most prevalent in the children particularly in developing countries like Pakistan. Statistics have revealed a horrible picture about children suffering from Protein Energy Malnutrition (PEM) and micronutrient deficiencies. Nonetheless, there is burgeoning demand for nutrient dense foods. In this perspective, nutritional value of the biscuits was enhanced by supplementing wheat flour with lentil and oat flour (5, 10, 15, 20 and 25%). Chemical composition of different flours indicated that oat flour had higher ash and fiber content, whereas highest fat and protein were reckoned in lentil flour. The composite flour (WF: LF: OF; 50: 25: 25) showed highest concentrations of nutrients like ash (3.76%), fat (4.09%), fiber (2.96%) and protein (12.50%). Addition of supplement flour shad significantly affected the dough rheological properties. Nutrient composition of lentil-oat supplemented biscuits evaluated in terms of moisture (3.22-4.30%), ash (0.45-1.71%), fat (19.71-27.40%), fiber (0.20-2.56%) and protein (5.44-8.90%), carbohydrate (56.64-69.80%), iron (3.3-5.90 mg/100g), zinc (0.56-3.59 mg/100g) and energy value (528.26-588.76 Kcal). Spread factor of such biscuits varied between 45.90 and 56.00. The highest acceptability for biscuits was observed when wheat flour was supplemented with lentil and oat flour at 15% level.